HBV reactivation during immunotherapy for hepatocellular carcinoma: risk factors and clinical management - Jin, Yurou; Jin, Chao; Xie, Ronghui; Zhang, Jingming; Wei, Guangmin; Zheng, Ling (Frontiers in Immunology, 2026)
Hepatitis B virus reactivation (HBVr) poses a serious clinical challenge and potentially life-threatening complication in patients with hepatocellular carcinoma (HCC), particularly amid the expanding use of modern immunotherapeutic agents. Despite progress in antiviral prophylaxis and refined risk-stratification strategies, HBVr continues to compromise treatment efficacy and survival outcomes, especially in patients receiving immune checkpoint inhibitors, tyrosine kinase inhibitors, or combination regimens. This review comprehensively synthesizes current evidence on the virological foundations, clinical risk factors, and immunopathological mechanisms underpinning HBVr during HCC treatment, emphasizing the pivotal roles of covalently closed circular DNA (cccDNA) persistence and treatment-induced immune dysregulation. We further examine the comprehensive evidence of risk factors in HBVr, including various treatments for HCC. We also reviewed the clinical consequences of HBVr, including acute hepatocellular injury, unplanned treatment discontinuations, and adverse long-term HCC prognosis. Evidence-based management approaches, such as universal serological screening, individualized antiviral prophylaxis, and multidisciplinary coordination, are detailed to effectively reduce reactivation risk. Finally, we discuss emerging therapeutic strategies, including HBV-specific cellular therapies and innovative siRNA-based and immunostimulatory cytokine delivery platforms, which offer promising avenues for eradicating viral reservoirs and restoring immune surveillance.